Predictors of neuropsychiatric manifestations in pediatric patients with lupus - Wei Jiang; Xin Peng; Liqun Dong; Ling Wu; Yazhen Di; Li Lin (PLoS ONE, 2025)
Early detection of neuropsychiatric systemic lupus erythematosus (NPSLE) in children remains challenging in clinical settings. This study aims to describe the autoantibodies, organ disorders, the SLEDAI-2K score, and complement levels at the time of diagnosis in systemic lupus erythematosus (SLE) as well as investigate the predictors of NPSLE. We reviewed medical records of hospitalized children with SLE (< 18 years old) and extracted information on clinical features, serum autoantibodies, and laboratory test results. Multivariable logistic regression was used to establish the predictors of NPSLE and SLE without neuropsychiatric manifestations. Results revealed that 22.8% of children with NPSLE had higher ANA levels and SLEDAI-2K scores, lower C4 levels, and greater AMA-M2, β2GPI Abs, Anti-Rib-P Ab, ANCA, and LAC positivity at SLE diagnosis. The predictors of NPSLE were β2GPI-Abs (OR = 4.603), anti-Rib-P Ab (OR = 4.153), and SLEDAI-2K score (OR = 1.215). In summary, the findings show that the SLEDAI-2K score, β2GPI-Abs, and anti-Rib-P Ab are predictors of NPSLE.